Effects of yawed inflow on the dynamic performance of suction caisson-supported offshore wind turbines via wind tunnel tests - Yixiao Chen; Hongjun Liu; Kun Lin; Annan Zhou (Soil Dynamics and Earthquake Engineering, 2027)

Effect of magnetic field treatment on the structural and aggregation behavior of gluten, gliadin, and glutenin in potato pulp enriched dough - Jialin Song; Feng Han; Ying Sun; Dongliang Zhang; Shanfeng Chen; Hongjun Li (Innovative Food Science & Emerging Technologies, 2026)

Biomass-derived 3D solar evaporator with enhanced sterilization performance for seawater desalination and wastewater treatment - Siqi Wang; Shuang Wang; Hongjun Chen; Pengjie Xian; Huang Zhou (Desalination, 2026)

Instant CMQT stabilization coupled UHPLC-MS/MS for the quantification of reduced and total forms of cysteine, homocysteine, and glutathione in blood plasma - Yongyin Zhou; Haizhu Tan; Yingtong Chen; Hongjun Luo; Hui Li; Wenhong Luo; Yingxiu Xiao; Zhexuan Lin (Analytica Chimica Acta, 2026)

A novel two-layered hydroxyapatite-strengthened anammox-partial denitrification/anammox reactor for advanced nitrogen removal : Performance and mechanisms - Shenghao Ji; Hongjun Zhao; Shen Cui; Yujie Chen; Haojie Qin; Kengo Kubota; Jianyong Liu; Yu-You Li (Water Research, 2026)

Tire wear particles in the environment: A critical review on key challenges and future perspectives in fate, risk, and mitigation - Niling Zou; Hongjun Xiao; Gaoju Zou; Dehua Du; Zhen Liu; Shixin Zhang; Jiayue Zhu; Fan Yang; Kaifeng Wang; Anke Du; Yao Chen (Journal of Water Process Engineering, 2026)

Reprogramming oily water separation with Janus membranes: From asymmetric fabrication to engineering perspectives - Mingyi Ying; Bisheng Li; Jiaheng Teng; Xiang Cai; Cheng Chen; Leihong Zhao; Hongjun Lin (Journal of Environmental Chemical Engineering, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Interfacial energy homogenization enables β-phase transition and high piezoactivity in MOF/PVDF membrane for sustainable pollutant degradation - Zi Yang; Miaomiao Tian; Cheng Chen; Zhiyu Zhao; Libo Zhao; Jiujing Xu; Wei Yu; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Construction of MOF-decorated 3D printed membrane with hierarchical surface functionalization for oil-water separation: Role of interfacial energy barrier - Jingtao Hu; Zhiyu Zhao; Hua Li; Saleem Raza; Ying Liu; Cheng Chen; Wei Yu; Yanchao Xu; Hongjun Lin; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2026)

Catechol-based synergistic antioxidant nanoplatform for alleviating cisplatin-induced hearing loss - Yunni Tu; Bo Liu; Congshu Feng; Yaqin Tu; Hang Yan; Zilong Chen; Jinghang Li; Youfa Wang; Hongjun Xiao; Lesan Yan (Chemical Engineering Journal, 2026)

Deep Immunophenotyping Unravels the Double Negative T cells and PD-1-Mediated Inflammatory Exhaustion in Ankylosing Spondylitis - Lu Bai; Jian Gao; Yunyun Xu; Yuexin Yu; Jing Liu; Mathias Hochgerner; Hejian Zou; Xingdong Chen; Feng Qian; Hongjun He; Jiucun Wang (Phenomics, 2026)
Ankylosing spondylitis (AS) is a chronic, immune-mediated inflammatory disorder primarily affecting the axial skeleton. It is characterized by bony fusion and syndesmophyte formation of the spine, leading to compromised mobility, reduced quality of life and increased mortality. However, the underlying immune dysregulation in AS remains poorly understood. We comprehensively profiled the peripheral immune landscape of 30 patients with active AS, all of whom were TNF-α blocker-naïve, capturing the immune profile during the active disease phase without biologic interference. Using advanced 11-color flow cytometry and FlowSOM clustering, 584 immunophenotypes were analyzed in AS and 30 age-and sex-matched healthy controls, with emphasis on both cellular composition and functional characteristics. AS patients displayed a distinctive functional “activated-exhausted” immune phenotype, dominated by CD4 + CD28 + CD38 + PD-1 + T cells and HLA-DR + CD38 + CD4 − CD8 − double-negative (DN) T cells. DN T cells were significantly enriched in HLA-B27-positive patients, suggesting potential as a biomarker. Network analysis revealed seven central immune subsets associated with active disease, while functional assessment demonstrated impaired CD95 + CD8 + T cell apoptosis and disrupted B-cell maturation. These findings provide a detailed functional immune map of biologic-naïve active AS, offering novel mechanistic insights and identifying candidate biomarkers for precision intervention.

Adsorption and ligand-to-metal charge transfer (LMCT)-driven photodegradation of PFOA/PFOS by iron-based materials: Mechanistic insights and environmental risk analysis - Tao Jian; Bisheng Li; Cheng Chen; Leihong Zhao; Xiang Cai; Hongjun Lin; Xiaohong Guan (Critical Reviews in Environmental Science and Technology, 2026)

Ultrasound-targeted cavitation induced tumor vascular normalization and radiotherapy sensitization in breast cancer - Zichao Liu; Huai Yang; Zenan Zhang; Chenke Kuang; Liyong Deng; Yueyong Li; Linyuan Jin; Hongjun Nie; Guihua Wang; Meng Du; Zhiyi Chen (Science China Life Sciences, 2026)

Form-dependent chloroform adsorption behavior from powdered to sintered carbon - Qing Gao; Zhilong He; Jianjun Cheng; Jingwen Li; Dapeng Zhou; Jiahua Shi; Xiuli Chen; Hongjun Liu (Journal of Environmental Chemical Engineering, 2026)

Tire wear particles induce a functional trade-off in bioretention systems: Coupled effects on nitrogen removal and greenhouse gas emissions - Gaoju Zou; Niling Zou; Yinghui Tang; Qinyi Wang; Hongjun Xiao; Quanhong Chen; Zhen Liu; Kaifeng Wang; Fan Yang; Huachao Zhao; Yu Qin; Anke Du; et al. (Environmental Research, 2026)

Influence of aspect ratio on the dynamic performance of suction caisson supported wind turbines: insights from wind tunnel tests - Yixiao Chen; Kun Lin; Annan Zhou; Hongjun Liu (Ocean Engineering, 2026)

Trade-off in bioretention: Tire wear particles mitigate sulfamethoxazole toxicity but exacerbate antibiotic resistance propagation - Quanhong Chen; Niling Zou; Yinghui Tang; Hongjun Xiao; Gaoju Zou; Kaifeng Wang; Jiayue Zhu; Zhen Liu; Dehua Du; Yu Qin; Anke Du; Yao Chen (Journal of Water Process Engineering, 2026)

Synergistic mechanism of low-frequency magnetic field on structural and functional benefits from homologous binding of potato protein and purple potato anthocyanins - Fengzhang Lv; Miao Wang; Yingjie Lv; Xin Xu; Yilin Wang; Chengye Ma; Shanfeng Chen; Hongjun Li; Chenjie Wang (Food Chemistry, 2026)

Generation and characterization of the monoclonal antibody against the heavy chain of American eel (Anguilla rostrata) IgM - Xiaolong Meng; Shuangshuang Cao; Hongjun Xie; Wenting Jiang; Rui Guo; Yuchen Zhuo; Qicheng Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2026)

Targeting delivery of shikonin via cryo-shocked tumor cells for non-small cell lung cancer treatment - Huanhuan Huang; Hui Ren; Feiye Liu; Wenyue Lv; Mengzhen Xu; Huiheng Feng; Haoli Liu; Dong Chen; Peng Zhao; Hongjun Li; Jing Qin (Chemical Engineering Journal, 2026)

Mitigating PM2.5 exposure and health impacts for school-aged children: The role of street canyon layouts and greenery design - Chen Ren; Chang Xi; Yaru Meng; Hongjun Zhang; Mingming Zhao; Shi-Jie Cao (Urban Climate, 2026)

Synergistic integration of NiFe-MOF and carbon quantum dots for multifunctional nanofiltration membranes with high permeability and photocatalytic self-cleaning - Zhao Chen; Yifan Liu; Hongyuan Zhu; Haiyi Jin; Shasha Yuan; Die Ling Zhao; Hongjun Lin (Desalination, 2026)

Monsoon and sea-level induced environmental shifts in the Bohai Sea, East Asia during the early-middle Pleistocene - Nanze Liang; Yibing Li; Yan Li; Haifeng Wang; Hongjun Yu; Xingyong Xu; Qiao Su; Xingyu Jiang; Guangquan Chen; Tengfei Fu; Weiwei Chen; Liang Yi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mineral-associated organic carbon promotes phosphorus accumulation in a long-term fertilized black soil - Naiyu ZHANG; Xiuzhi ZHANG; Yanhua CHEN; Lehlogonolo Abner MATELELE; Ping ZHU; Hongfang LIU; Xianmei ZHANG; Hongjun GAO; Gu FENG; Chang PENG; Shuxiang ZHANG (Pedosphere, 2026)

Liquid fuel intrusion causes carbon canister deterioration and excess evaporative VOC emissions from in-use vehicles - Pengfei Song; Yan Liu; Qiang Chen; Jingyu Liu; Xueying Zeng; Tianlong Xing; Rui Zhang; Chongzhi Zhong; Taiyu Zhang; Ning Yang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Dual-function tara gum-based antiscalant with efficient antiscaling and antibacterial activity: Performance and molecular simulation investigation - Liping Xiong; Wei Yu; Xinyi Lu; Zhiyu Zhao; Cheng Chen; Renjie Li; Guanhua Jin; Leihong Zhao; Hongjun Lin; Liguo Shen (Journal of Environmental Chemical Engineering, 2026)

Dynamic performance of suction caisson supported offshore wind turbines under different operational conditions - Kun Lin; Yixiao Chen; Annan Zhou; Hongjun Liu (Engineering Structures, 2026)

Bioaccumulation and trophic transfer of PAHs in the Yellow River Estuary food web: A fugacity-based model for ecological and human health risk assessment - Xin Liu; Xuguang Hong; Hongjun Song; Degang Wang; Kan Chen; Jiachen Sun; Zhaohui Zhang; Jiansong Chu (Marine Pollution Bulletin, 2026)

Late Quaternary evolution of lower course river sections and coastal plains in the southwestern Hainan Island, South China Sea - Ryszard Krzysztof Borówka; Jakub Miluch; Łukasz Maciąg; Andrzej Osadczuk; Tao Jiang; Hongjun Chen; Jan Harff; Michał Tomczak; Krystyna Osadczuk; Karolina Bloom; Jinpeng Zhang; Changliang Tong (Quaternary International, 2026)

Performance enhancement evaluation of coal gangue aggregates based on chemical solution modification: mechanical properties and microstructural characteristics - Meng Gao; Hongjun Jing; Jun Dai; Shaojie Chen; Chaowei Zhang; Junwei Shan; Hengfei Zhang; Yuanquan Cui; Shixuan Lei (Chemical Engineering Journal, 2026)

In-situ assembly of vertically-grown SnS2 nanosheets on TiO2 microspheres for efficient photocatalytic nitrogen fixation - Huijun Liang; Xinyu Wang; Yuanyuan Ji; Xin Li; Xiang Zhen; Jianxun Dong; Feijian Lou; Hongjun Chen; Zhichao Jia; Huiran Zhou; Xiaobing Wang (Fuel, 2026)

Triatomic-doped MXene based catalyst with sodium alginate encapsulation their molecular and DFT calculation study for efficient photocatalytic removal of disinfected by-product from drinking water - Saleem Raza; Ata Ur Rehman; Zhiyu Zhao; Hua Li; Cheng Chen; Wei Yu; Ying Liu; Yanchao Xu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Linear diacyl chloride enables polyamide nanofiltration membranes with balanced permeability and selectivity for efficient dye desalination - Jiujing Xu; Cheng Chen; Zhiyu Zhao; Leihong Zhao; Wei Yu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

A new tyrosine derivative isolated from an actinomycin D producing mangrove rhizosphere soil-derived Streptomyces parvulus A-30 - Jingjing Ye; Juren Cen; Jingwan Wu; Zhenchang Wen; Hongjun Chen; Jing Xu (Natural Product Research, 2026)

Escalating landscape fire exposure and its deteriorating global equity: Role of associated population changes, socioeconomic levels, and climate changes - Tong Pan; Hongjun Wang; Jiyuan Chen; Zipei Fan; Xuan Song (Science of The Total Environment, 2026)

A crack detection system for underwater marine structures based on an improved YOLOv12 model - Hongquan Li; Fei Kang; Xianyu Zhu; Jing Chen; Hongjun Li (Ocean Engineering, 2026)

Unveiling the microplastic migration behavior in riverine systems: hydrodynamic impacts on transport and sedimentation - Kaifeng Wang; Quanhong Chen; Qiming Cheng; Yuqing Tan; Wenyu Xiao; Yihong Su; Fei Liu; Hongjun Xiao; Ye Rao; Zhen Liu; Yao Chen (Journal of Hydrology, 2026)

Proline-functionalized zein nano delivery system enables sustained brassinolide release for enhanced salt stress tolerance in cucumber cultivation - Jihao Zuo; Ruopeng Lan; Jinting Cai; Long Chen; Dongyan Yang; Huayao Chen; Li Hao; Ximing Zhong; Xinhua Zhou; Hongjun Zhou (Chemical Engineering Journal, 2026)

Alternating current or direct current: Which is better for electrochemical membrane separation water purification system? - Zhen Qiu; Jiujing Xu; Cheng Chen; Wei Yu; Bisheng Li; Liguo Shen; Bing Yu; Huajun Feng; Hongjun Lin (Chemical Engineering Journal, 2026)

Hydrogen-bonded organic framework enables ultrathin polyamide membrane for efficient endocrine disrupting compounds removal - Jiujing Xu; Xueyu Wang; Cheng Chen; Rukang Jiang; Boya Wang; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin; Banglin Chen (Chemical Engineering Journal, 2026)

Lacticaseibacillus paracasei subsp. paracasei Q- 1 Exhibits Good Safety and Effectively Prevents Escherichia coli K99-Induced Diarrhea in Mice - Fengjie Wang; Li Chen; Yang Li; Guangping Gao; Yanan Wang; Ruili Shi; Hongjun Zhang; Yingyu Chen; Rui Cao; Qiumei Shi; Tonglei Wu (Probiotics and Antimicrobial Proteins, 2026)

Robust trajectory tracking control of lunar rovers considering wheel-terrain slip - Yuzhe Xu; Hongjun Xing; Yanqing Liu; Jinyao Zhu; Jinbao Chen; Liang Ding (Advances in Space Research, 2026)

A modified curve number method for runoff prediction of different vegetation types at the slope scale in China - Jinle Yu; Hongjun Chen; Miaomiao Wang; Jiachi Bao; Wenyi Song; Xitong He; Wenhai Shi (Soil and Tillage Research, 2025)

Assessing the spatial-temporal wave energy characteristics along the southeastern coast of China in a wave simulation study - Jie Yang; Chen Wang; Hongjun Zhao (Ocean Engineering, 2025)

Crossflow-induced vibration of a near-wall cylinder behind another of smaller diameter - Guanghao Chen; Md. Mahbub Alam; Yu Zhou; Hongjun Zhu; Chunning Ji; Junlei Wang; Md Islam; Mostafa Zeinoddini (Ocean Engineering, 2025)

The sedimentary provenance of Upper Miocene Dongfang submarine fan, Yinggehai Basin: source-to-sink system unravelled through new detrital zircon U-Pb ages and heavy mineral analysis - Xingzong Yao; Congjun Feng; Wei Zhou; Pengfei Wu; Hongjun Qu; Jiahao Lei; Zhiqiang Chen; Yanlong Ge; Mengsi Sun (Marine and Petroleum Geology, 2025)

Enhanced built-in electric field and strong interfacial electronic coupling in 2D/2D BiO2-x/Ti3C2 Schottky heterojunction boost exciton dissociation for sustainable molecular oxygen activation toward 100 % singlet oxygen generation - Chongyang Yang; Song Tian; Yanyan Liu; Liguo Shen; Cheng Chen; Yanchao Xu; Leihong Zhao; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Submarine groundwater discharge derived metal elements fluxes in a seawater intrusion influenced area - Yancheng Wang; Guangquan Chen; Wenzhe Lyu; Xinbin Zhao; Chutima Boonyaridsripong; Shengfa Liu; Hongjun Yu; Xingyong Xu (Journal of Environmental Sciences, 2025)

Ultrasound-assisted fermentation of doughs enriched with 7S and 11S soy protein fractions: impacts on quality and protein–protein interactions - Feng Han; Ying Sun; Jialin Song; Xin Zhang; Chuangshuo Yan; Yufan Wang; Shanfeng Chen; Chengye Ma; Hongjun Li (Food Research International, 2025)

Thiol-ene click synthesis of a novel alginate-derived adsorbent: Synergistic adsorption and mechanistic investigation of dye and antibiotic - Xinyi Lu; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Guanhua Jin; Leihong Zhao; Saleem Raza; Liguo Shen (Desalination, 2025)

Enzymatically degradable pesticide microcapsules fabricated from zein nanoparticle-stabilized Pickering emulsions for enhanced safety and prolonged crop protection - Long Chen; Huahui Ren; Liang Li; Jihao Zuo; Jinting Cai; Ying Li; Huayao Chen; Li Hao; Hongjun Zhou; Zhanghua Zeng; Xinhua Zhou (Chemical Engineering Journal, 2025)

Soil carbon dioxide dynamics in deep profiles under erosional and depositional conditions on the Chinese Loess Plateau - Jiachi Bao; Tiantian Chen; Wenyi Song; Miaomiao Wang; Hongjun Chen; Jinle Yu; Wenhai Shi (CATENA, 2025)

The key mechanism of improving nitrogen fertilizer utilization in greenhouse pepper through aerated drip irrigation: stimulating soil enzyme activity and affecting soil carbon pool - Yecheng Dong; Hongjun Lei; Zhifang Lv; Chen Yin; Zheyuan Xiao; Hongwei Pan; Yingji Lian (Plant and Soil, 2025)

Dynamic Compaction Resistance Model Considering Stone Block Shape Effects - Xiong Bobo; Li Hongjun; Tian Bin; Chen Bofu; Zheng Qian; Li Chen; Zhang Jingkang (Geotechnical and Geological Engineering, 2025)

Decoupling and decomposition analysis of industrial carbon emissions, and projection of its future trends: A case study of Quanzhou, China - Yanxi Tang; Jing Xu; Muping Shen; Jiachang Zuo; Fengyi Yu; Yingmao Tang; Tingting Liu; Hongjun Jin; Yongjin Luo; Qingrong Qian; Qinghua Chen (Environment, Development and Sustainability, 2025)

Molecular insights in outstanding performance of Ca2+ bridging MXene/Sodium alginate composite membranes - Hua Li; Hongjun Lin; Saleem Raza; Zhiyu Zhao; Siyuan Chen; Yue Wang; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Water Research, 2025)

Efficient preparation and structural characterization of theabrownins from fermented summer green tea with Aspergillus cristatus (MK346334) in submerged fermentation - Jingqian Zheng; Jiayue Fang; Hongjun Liu; Zhiyong Xie; Xia Fan; Guijie Chen; Xiaoxiong Zeng (Food Chemistry, 2025)

Magnetic-field-assisted fabrication of Fe3O4-enhanced thin-film nanocomposite polyamide nanofiltration membranes with enhanced separation performance - Congcong Zhou; Zhihao Chen; Jingfen Yuan; Yang Jiao; Hongjun Lin; Yanchao Xu (Desalination, 2025)

Double cross-linking architectonics membranes for high-efficiency oil-water separation and the mechanistic investigation - Yue Wang; Hongjun Lin; Siyuan Chen; Hua Li; Zhiyu Zhao; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2025)

Magnetically directed interfacial polyamerization of Fe3O4@CdS@CQDs-embedded polyamide nanofiltration membranes with enhanced separation and photocatalytic self-cleaning performance - Erqiao Chen; Zhihao Chen; Zhongting Liu; Mingzhu Zhou; Bisheng Li; Renjie Li; Liguo Shen; Yang Jiao; Hongjun Lin; Yanchao Xu (Chemical Engineering Journal, 2025)

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Preliminary Feasibility Study of Using Hydrogen as a Fuel for an Aquaculture Vessel in Tasmania, Australia - Hongjun Fan; Peggy Shu-Ling Chen; Andrew Harris; Nagi Abdussamie; Evan Mac A. Gray; Irene Penesis; Javad A. Mehr (Journal of Marine Science and Engineering, 2025)
Decarbonising aquaculture support vessels is pivotal to reducing greenhouse gas (GHG) emissions across both the aquaculture and maritime sectors. This study evaluates the technical and economic feasibility of deploying hydrogen as a marine fuel for a 14.95 m net cleaning vessel (NCV) operating in Tasmania, Australia. The analysis retains the vessel’s original layout and subdivision to enable a like-for-like comparison between conventional diesel and hydrogen-based systems. Two options are evaluated: (i) replacing both the main propulsion engines and auxiliary generator sets with hydrogen-based systems—either proton exchange membrane fuel cells (PEMFCs) or internal combustion engines (ICEs); and (ii) replacing only the diesel generator sets with hydrogen power systems. The assessment covers system sizing, onboard hydrogen storage integration, operational constraints, lifecycle cost, and GHG abatement. Option (i) is constrained by the sizes and weights of PEMFC systems and hydrogen-fuelled ICEs, rendering full conversion unfeasible within current spatial and technological limits. Option (ii) is technically feasible: sixteen 700 bar cylinders (131.2 kg H2 total) meet one day of onboard power demand for net-cleaning operations, with bunkering via swap-and-go skids at the berth. The annualised total cost of ownership for the PEMFC systems is 1.98 times that of diesel generator sets, while enabling annual CO2 reductions of 433 t. The findings provide a practical decarbonisation pathway for small- to medium-sized service vessels in niche maritime sectors such as aquaculture, while clarifying near-term trade-offs between cost and emissions.

3D-printed super-wetting membranes with in situ grown MOF for efficient oil-water separation - Siyuan Chen; Zhiyu Zhao; Cheng Chen; Wei Yu; Xinchun Lu; Yue Wang; Hua Li; Qianqian Zeng; Hongjun Lin; Leihong Zhao; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2025)

Biotransformation and toxicity attenuation of 2,6-Dichlorobenzoquinone in simulated human gastrointestinal conditions: Insights from a systematic in vitro study - Lili Zheng; Guolong Chen; Kuangtao Fu; Zhen Wang; Xinyue Yuan; Hongjie Sun; Wenjing Deng; Zeqiong Xu; Hongjun Lin; Huachang Hong (Journal of Hazardous Materials, 2025)

Facile fabrication of MnCO3 and covalent organic framework on the surface of MXene with sodium alginate hydrogel for effective photocatalytic eradication of disinfected byproducts - Saleem Raza; Cheng Chen; Wei Yu; Muslim Raza; Malik Taj Ahmad; Nisha Singh; Liguo Shen; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Homologous non-covalent binding mechanism of potato protein and purple potato anthocyanins: Insights into structural and functional benefits - Fengzhang Lv; Miao Wang; Xin Xu; Yilin Wang; Ruoyun Yuan; Chengye Ma; Shanfeng Chen; Hongjun Li; Chenjie Wang (Innovative Food Science & Emerging Technologies, 2025)

Novel CoMo-LDH integration enhanced permeability and self-cleaning of MXene-based membrane for efficient water treatment - Qianqian Zeng; Zhiyu Zhao; Yue Wang; Siyuan Chen; Hua Li; Cheng Chen; Wei Yu; Jiaheng Teng; Hongjun Lin; Yu Yang; Liguo Shen (Chemical Engineering Journal, 2025)

Stable molecular-bridged graphene oxide membrane with bioinspired hydrophilic water inlets for ultrafast molecular separation - Boya Wang; Cheng Chen; Wei Yu; Jiujing Xu; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Optimization of up-flow velocity enhances the performance of partial denitrification/anammox process in expanded granular sludge bed reactor based on the formation of hydroxyapatite - Shenghao Ji; Shen Cui; Hongjun Zhao; Haojie Qin; Yu Qin; Yujie Chen; Yu-You Li (Chemical Engineering Journal, 2025)

Cobalt-doped zinc phosphides regulated by phytic acid effects on the electrochemical activity of sensing clothianidin - Peiyuan Wei; Wei Han; Lingling Xie; Hongjun Chen; Yuling Wang; Limin Zhu; Baoshan He; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Controls of paleosedimentary environments and anthropogenic activities on coastal groundwater salinization: A case study of Laizhou Bay, China - Zhen Cui; Guangquan Chen; Xin Shan; Haitao Zhang; Qingjie Zhou; Tengfei Fu; Hongjun Yu; Xingyong Xu; Shenliang Chen (Marine Geology, 2025)

Hybrid machine learning model with SHAP interpretability for optimization of targeted nitrogen and phosphorus removal from bioretention systems - Ying Yuan; Quanhong Chen; Yinghui Tang; Qiming Cheng; Gaoju Zou; Xiaoke Lian; Zhen Liu; Hongjun Xiao; Mingyue Liu; Kaifeng Wang; Shixin Zhang; Yao Chen (Journal of Water Process Engineering, 2025)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Deciphering the nexus of soluble microbial products (SMPs) and membrane fouling: Roles, mechanisms, and control strategies - Xinyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Jiaheng Teng; Meijia Zhang; Bisheng Li; Leihong Zhao; Die ling Zhao; Cheng Chen (Chemical Engineering Journal, 2025)

Declining floral color diversity alters bee color preferences in fragmented habitats - Hongjun Xie; Peng Ren; Chen Zhu; Juan Liu; Minghao Sun; Xingfeng Si; Ping Ding (Biological Conservation, 2025)

Bio-derived carboxymethyl cellulose-graft-gallic acid antiscalant with remarkable antibacterial activity for reverse osmosis scaling and biofouling control - Liping Xiong; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Liguo Shen (Water Research, 2025)

Rice-fish coculture without phosphorus addition improves phosphorus availability in paddy soil by regulating phosphorus fraction partitioning and alkaline phosphomonoesterase-encoding bacterial community - Xing LIU; Yuting CHEN; Hongjun ZHENG; Daolin SUN; Jiaen ZHANG; Qi JIA; Qi CHEN (Pedosphere, 2025)

Reversing inhibition to promotion in phenol-ammonium metabolism via algal-microbial fuel cell: Mechanisms of phenol-ammonium interaction and synergistic removal - Yaqi Liu; Mengqi Zheng; Longyi Lv; Guowei Chen; Chengye Wang; Zhenhu Hu; Jingwei Feng; Binghan Xie; Hongjun Han; Wei Wang (Journal of Hazardous Materials, 2025)

Alternating current electrochemistry for energy-efficient contaminant removal and resource recovery in water treatment: A critical review - Chengyue Yu; Cheng Chen; Mingzhu Zhou; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Antibacterial properties of folic acid-based hydrogel loaded with CeCDs and its potential application in food preservation - Mengzhen Wang; Li Zeng; Hongjun Chen; Senhao Hu; Chengzhi Huang; Shujun Zhen; Lei Zhan (Food Chemistry, 2025)

Direct visual detection for methicillin-resistant Staphylococcus aureus in milk based on the RPA-Cas12a-LFS method - Yixiang Sun; Liren Zhang; Huimin Wu; Hongjun Chen; Huijie Hu; Chongyu Zhang; Xiaoqiang Li; Yuan Li; Yimai Wang; Liqiang Luo; Yizhi Song (Food Control, 2025)

Optimizing Lancang-Mekong hydropower portfolio effectively reduces greenhouse gas emissions - Xiaobo Yun; Qiuhong Tang; Jie Wang; Siao Sun; Hongjun Bao; Yadu Pokhrel; Lifeng Luo; Deliang Chen (Environmental Impact Assessment Review, 2025)

The role of SYK phosphorylation in LPS-induced immunoglobulin responses of B cells in large yellow croaker (Larimichthys crocea) - Hongjun Xie; Shuangshuang Cao; Yueming Chen; Zhiqiang Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Application of construction waste residue-based compositing fillers in bioretention facility: Intensified nitrogen removal and mitigated by-product effects - Xiaoke Lian; Yinghui Tang; Qiong Wu; Hongjun Xiao; Jianhua Ni; Ying Yuan; Qiyi Wang; Zhen Liu; Gaoju Zou; Shixin Zhang; Chaohan Meng; Yao Chen (Environmental Research, 2025)

A modified curve number method for runoff prediction of different soil types in China - Miaomiao Wang; Yangdong Zhao; Wenhai Shi; Jinle Yu; Tiantian Chen; Jiachi Bao; Wenyi Song; Hongjun Chen (CATENA, 2025)

On the capability of SWAN model for South Atlantic Ocean wave simulation - Hongjun Zhao; Peixian Chen; Wanwei Zhang; Shichang Yan; Jie Yang; Jun Kong (Ocean Dynamics, 2025)

Aerated Drip Irrigation: A Sustainable Approach to Improving Soil Environment, Crop Growth, Quality, and Yield in Greenhouse Cultivation - Yecheng Dong; Hongjun Lei; Zheyuan Xiao; Cuicui; Jin; Yingji Lian; Hongwei Pan; Zhengjun Zhang; Chen Yin; Keping Sun (Journal of Soil Science and Plant Nutrition, 2025)

Diversity and Function of Strawberry Endophytic Bacterial Communities Associated with Host Genotype and Niche - Hongjun Yang; Xu Zhang; Zhiming Yan; Yuanhua Wang; Quanzhi Wang; Bei Lu; Jiajia Chen; Xiao Wu (Current Microbiology, 2025)

Integrated process of Tetrasphaera-dominated enhanced biological phosphorus removal and sulfur autotrophic denitrification in a single reactor to treat VFAs-free wastewater: Feasibility, performance and mechanism - Hongjun Liu; Wei Zeng; Gangxin Chen; Qingan Meng; Jiayu Zhang; Zhaoyang Bi; Yongzhen Peng (Journal of Water Process Engineering, 2025)

Exploring the regulation of metabolic changes mediated by different combined starter cultures on the characteristic flavor compounds and quality of Sichuan-style fermented sausages - Buzhou Xu; Wenliang Qiu; Yuwei Liu; Fanyi Gong; Qian Liu; Jiaxin Chen; Yong Tang; Chang Su; Jie Tang; Dong Zhang; Hongjun Li (Food Research International, 2025)

FePS3-Nanosheets-Integrated multifunctional nanocomposite hydrogel for multimodal synergistic osteosarcoma therapy and enhanced bone regeneration - Bing Ye; Xirui Jing; Yanlin Su; Wenzhe Sun; Qing Gao; Lian Zeng; Hongwei Lu; Shuo Tang; Yizhou Wan; Tingfang Sun; Zekang Xiong; Xiao Lv; et al. (Chemical Engineering Journal, 2025)

Effect of ultrasound-assisted phosphates treatment on solubilization and stable dispersion of rabbit Myofibrillar proteins at low ionic strength - Chang Su; Yuxin Huang; Jiaxin Chen; Hongjun Li; Dong Zhang; Yong Tang (Food Chemistry, 2025)

Multifactorial Controls on the Dongdaobei Submarine Canyon System, Xisha Sea, South China Sea - Meijing Sun; Hongjun Chen; Chupeng Yang; Xiaosan Hu; Jie Liu (Journal of Marine Science and Engineering, 2025)
The submarine canyons system is the most widely distributed geomorphic unit on the global continental margin. It is an important concept in the field of deep-water sedimentation and geohazards. Based on high-resolution multibeam bathymetry and two-dimensional seismic data, the dendritic canyon system north of Dongdao island is studied at the eastern Xisha area of the South China Sea. The Dongdaobei submarine canyon is distributed in water depths between 1000 and 3150 m. The main source area in the upper course of the canyon originates from the northwest of Dongdao platform and the Yongxing platform. The sediments from the source area are transported to the main canyon in the form of various gravity flows. Landslides on the slope significantly impact canyon evolution by delivering sediment to the canyon head and causing channel deflection through substrate failure and flow-path reorganization. A large number of pockmarks are distributed around the north slope of the main canyon. The small-scale channels, which are formed as a result of the continuous erosion of the pockmark chains, are connected to the canyon sidewalls. The seamounts are distributed along the south bank of the canyon, exerting a controlling influence on the directional changes in the main canyon’s downstream segment. The formation and evolution of the Dongdaobei submarine canyon are primarily influenced by several factors, including tectonic activity and inherited negative topography, erosion by sedimentary gravity flows, sediment instability, and the shielding effect of seamounts.

The relationship between high-quality development and ecosystem health in China's urban agglomerations - Bin Yang; Xiaohan Ma; Jirong Li; Haochen Yu; Hongjun Sui; Fu Chen; Li Tan (Journal of Environmental Management, 2025)

A novel method to improve the anti-ageing ability of bitumen by organic LDHs/SBS composite: Preparation, performance evaluation and mechanism analysis - Canlin Zhang; Shuai Yang; Ting Wang; Song Xu; Peng Jin; Hongjun Dong; Yi Zhang; Yu Chen (Fuel, 2025)

Molecular characterization of large yellow croaker (Larimichthys crocea) coagulation factor Ⅶ-like and its function on macrophage proliferation and polarization - Yueming Chen; Han Zhao; Shuangshuang Cao; Hongjun Xie; Jieyu Huang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

An improved curve number for runoff prediction under different vegetation pattern at slope scale in China - Wenhai Shi; Miaomiao Wang; Jiachi Bao; Jinle Yu; Tiantian Chen; Wenyi Song; Hongjun Chen (CATENA, 2025)

A single-atom manganese nanozyme mediated membrane reactor for water decontamination - Jiahao Sun; Minjia Yan; Guangdong Tao; Runbin Su; Xuanming Xiao; Qiangshun Wu; Feng Chen; Xi-Lin Wu; Hongjun Lin (Water Research, 2025)

Strengthening peroxymonosulfate activation via cotton-derived carbon: Pathway transformation from radical to non-radical - Runbin Su; Yonglin Ma; Lei Liu; Qiangshun Wu; Du Fu; Yu Li; Hongjun Lin; Xiaoxuan Wei; Muhammad Saboor Siddique; Jianrong Chen; Xi-Lin Wu (Journal of Cleaner Production, 2025)

Novel insights into halogenated carbazoles (HCZs) prediction in tap water: A comparative study of grey relational analysis-based neural networks - Qianfeng He; Wanting Xu; Guolong Chen; Zhen Wang; Yan Liang; Hongjie Sun; Huachang Hong; Hongjun Lin; Zeqiong Xu (Journal of Cleaner Production, 2025)

The heterointerface engineering triggers hydrogen spillover through synergistic effect in alkaline media - Qiang Zhang; Yuhong Bian; Sunpeng Shan; Zhiwei Shu; Nana Wang; Xiao Zhang; Yanchao Xu; Hongjun Lin; Jianrong Chen; Yang Jiao (Chemical Engineering Journal, 2025)

Extent of As(III) versus As(V) adsorption on iron (oxyhydr) oxides depends on the presence of vacancy cluster-like micropore sites: Insights into a seesaw effect - Juan Liu; Yixin Duan; Hao Chen; Bangjiao Ye; Hongjun Zhang; Wenfeng Tan; Andreas Kappler; Jingtao Hou (Science of The Total Environment, 2024)

Advancing anaerobic digestion with MnO2-modified biochar: Insights into performance and mechanisms - Yeqing Li; Jinglei Zhang; Xinran Wen; Mahmoud Mazarji; Shuo Chen; Qiang Liu; Shenggeng Zhao; Lu Feng; Gang Li; Hongjun Zhou; Junting Pan (Science of The Total Environment, 2024)

iRainSnowHydro v1.0: A distributed integrated rainfall-runoff and snowmelt-runoff simulation model for alpine watersheds - Yuning Luo; Ke Zhang; Yuhao Wang; Sheng Wang; Nan Wu; Shunzhang Li; Qinuo Zhang; Xinyu Chen; Hongjun Bao (Journal of Hydrology, 2024)

Microplastic transport and ecological risk in coastal intruded aquifers based on a coupled seawater intrusion and microplastic risk assessment model - Guangquan Chen; Yinqiao Zou; Guiyao Xiong; Yancheng Wang; Wenqing Zhao; Xingyong Xu; Xiaobin Zhu; Jichun Wu; Fan Song; Hongjun Yu (Journal of Hazardous Materials, 2024)

A novel application of industrial waste bischofite for the anti-aging property of asphalt: Synthesis of organic layered double hydroxide and performance evaluation - Hongjun Dong; Canlin Zhang; Yiwei Weng; Ting Wang; Song Xu; Shijie Ma; Shuai Yang; Yu Chen (Journal of Cleaner Production, 2024)

Super-hydrophilic membranes fabricated by synergistic integration of covalent organic framework nanoflowers and hydrophilic layers for efficient oil-water separation - Baoliang Dai; Yidan Ding; Cheng Chen; Liguo Shen; Die Ling Zhao; Yang Jiao; Hongjun Lin; Yanchao Xu (Desalination, 2024)

Recent progress in green thin film membrane based materials for desalination: Design, properties and applications - Saleem Raza; Asif Hayat; Tariq Bashir; Ehsan Ghasali; Amal A. Abdel Hafez; Cheng Chen; Liguo Shen; Yasin Orooji; Hongjun Lin (Desalination, 2024)

Optimization of fungal secondary metabolites production via response surface methodology coupled with multi-parameter optimized artificial neural network model - Hongjun Shu; Xiaona Chen; Qian Jiang; Yike Wang; Zhongyi Wan; Jinzhong Xu; Pinmei Wang (Bioresource Technology, 2024)

Enhancing Accuracy in Soil Water Content Measurement: A Modified Dielectric Model Approach - Hongjun Chen; Linze Li; Muhammad Awais; Mukhtar Iderawumi Abdulraheem; Wei Zhang; Vijaya Raghavan; Jiandong Hu (Journal of Soil Science and Plant Nutrition, 2024)

Drought risk assessment for maize/peanut intercropping based on crop model and SPEI - Yajiaoxue Guo; Zhanxiang Sun; Wei Bai; Zhe Zhang; Yue Zhang; Hongjun Du; Tianran Sun; Jinyu Zhang; Pu Peng; Yafei Ji; Qian Cai; Zhi Dong; et al. (Agricultural Systems, 2024)

Facile synthesis of defect-rich interfacial Mo/MoO2 for efficient peroxymonosulfate activation and refractory pollutants degradation - Hongjun Fang; Hui Guo; Xinzhen Feng; Zhaoxu Chen; Weijie Ji; Chak-Tong Au (Environmental Pollution, 2024)

Efficient nitrogen removal and stable operation of a dynamic membrane bioreactor (DMBR) for landfill leachate treatment - Jie Han; Wei Xu; Junjie Zhu; Xiaomei Su; Hailu Fu; Xiao Xiao; Feng Dong; Chongjun Chen; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2024)

Stimuli-responsive sulfur-containing amino acid functionalized boron nitride nanosheets as nanocarriers via improved adhesion to enhance antibacterial performance against plant diseases - Li Hao; Ziting Yin; Mei Guan; Qiangcheng Zheng; Zitao Feng; Jialin Zeng; Jinhui Wang; Huayao Chen; Jinhao Zhao; Hongjun Zhou; Xinhua Zhou (Chemical Engineering Journal, 2024)

Exploring source-specific ecological risks of PAHs near oil platforms in the Yellow River Estuary, Bohai Sea - Xin Liu; Xuguang Hong; Hongjun Song; Tong Zhang; Kan Chen; Jiansong Chu (Marine Pollution Bulletin, 2024)

Temporal-spectral-semantic-aware convolutional transformer network for multi-class tidal wetland change detection in Greater Bay Area - Siyu Qian; Zhaohui Xue; Mingming Jia; Yiping Chen; Hongjun Su (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Quasi-FeCo-MOF/CoS amorphous Nanosheets: A stable and highly active catalyst for electrocatalytic water splitting and monosaccharide oxidation - Yanqiu Xu; Qiang Zhang; Nana Wang; Lijun Huang; Xiao Zhang; Hongjun Lin; Yanchao Xu; Jianrong Chen; Yang Jiao (Chemical Engineering Journal, 2024)

Transcriptomics and Metabolomics Unveil the Neuroprotection Mechanism of AnGong NiuHuang (AGNH) Pill Against Ischaemic Stroke Injury - Liangliang Tian; Guangzhao Cao; Xiaotong Zhu; Lihan Wang; Jingyi Hou; Yi Zhang; He Xu; Lixia Wang; Shicong Wang; Chen Zhao; Hongjun Yang; Jingjing Zhang (Molecular Neurobiology, 2024)

Nonnegligible contribution of terrigenous sediment inputs from local small watersheds to west regions of the Pearl River Estuary, northern South China Sea shelf - Chenjian He; Tingping Ouyang; Mingkun Li; Shanying Zhu; Mingjie Yu; Shasha Peng; Zhaoyu Zhu; Yunpeng Wang; Hongjun Chen; Chengjing Tian (Marine Geology, 2024)

The development of an emotion lexicon for spicy food flavor experience - Lina Ren; Risu Na; Siyi Jiang; Darong Chen; Li Zhang; Hongjun Li; Pengfei Han (International Journal of Gastronomy and Food Science, 2024)

Mn-O bond Engineering Mitigating Jahn-Teller Effects of Manganese Oxide for Aqueous Zinc-ion Battery Applications - Meng Xie; Xiao Zhang; Ran Wang; Yang Jiao; Zhiwei Shu; Sunpeng Shan; Yuhong Bian; Hongjun Lin; Jianrong Chen; Yanchao Xu (Chemical Engineering Journal, 2024)

Interdecadal Change of the Relationship between Early Summer Precipitation over Northeast China and Spring Land Surface Thermal Anomalies in West Asia - Hongjun Sun; Haishan Chen; Xinguan Du; Yinshuo Dong (Journal of Meteorological Research, 2024)

Montmorillonite supported nano-silica and Schiff base ligands nanocomposite for agricultural antifungal agent with long-term sterilization ability - Li Man; Huayao Chen; Hongkai Deng; Hongjun Zhou; Li Hao; Xinhua Zhou (Applied Clay Science, 2024)

Seismic lithology and geological implications of pre-salt jurassic carbonate rocks in the Amu Darya Right Bank - Tang Yuzhe; Wang Hongjun; Zhang Liangjie; Chen Pengyu; Pan Xingming; Zhang Wenqi; Jiang Lingzhi; Xing Yuzhong; Wang Chen; Shan Yunpeng (Marine and Petroleum Geology, 2024)

Sedimentary evolution of the East China Sea with implications for the relationship between the East Asian winter and summer monsoon over the past 6.3 ka - Wenzhe Lyu; Tengfei Fu; Guangquan Chen; Qiao Su; Wenquan Liu; Yancheng Wang; Zhen Cui; Hongjun Yu; Xingyong Xu (Journal of Asian Earth Sciences, 2024)

Optimizing humic acid breakdown and methane production via semiconductor-assisted photo-anaerobic digestion - Qiang Liu; Haoyu Zhang; Shuo Chen; Yeqing Li; Mahmoud Mazarji; Lu Feng; Junting Pan; Hongjun Zhou; Chunming Xu (Chemical Engineering Journal, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Enhancing mechanism of extrusion pretreatment on bioconversion of distiller’s grains into microbial protein feed - Chenjie Wang; Yao Liu; Ruoyun Yuan; Ling Xu; Chunhui Xin; Yang Tang; Chengye Ma; Shanfeng Chen; Hongjun Li (Animal Feed Science and Technology, 2024)

Mg2+ addition: Unlocking optimized treatment performance and anti-fouling property in microalgal-bacterial membrane bioreactors - Fei Huang; Yu Zhao; Shilei Chen; Hongjun Lin; Jiaheng Teng; Xiang Cai; Meijia Zhang (Science of The Total Environment, 2024)

Modeling and 4E analysis of a new combined cooling, heating, and power energy system based on biogas combustion and hot oil for heat supply - Hongjun Tian; Xiaowei Chen; Sayed Fayaz Ahmad; Manoj Kumar Agrawal; Asiful H. Seikh; Nehad Ali Shah; Qiaolin Su (Process Safety and Environmental Protection, 2024)

Electricity-carbon coupling retail package optimization considering low-carbon benefits of distributed renewable energy - Hongjun Gao; Qianzhen Chen; Shuaijia He; Zhiyuan Tang; Haibo Li; Junyong Liu (Journal of Cleaner Production, 2024)

Simultaneously promoting CO2 permeability and selectivity of polyethylene oxide membranes via introducing CO2-philic KAUST-7 - Wen Hou; Jun Cheng; Yingyu Tan; Chen Yang; Xufeng Ren; Jinming Xie; Bangjiao Ye; Hongjun Zhang; Junhu Zhou (Fuel, 2024)

Improved grey principal component analysis neural network based adaptive thermal comfort model: Application in the enclosed cabin with microclimatic conditions - Siyu Chen; Hongjun Xue; Xiaoyan Zhang; Sina Dang; Jue Qu (Energy and Buildings, 2024)

Advances in synthesis and application of amphoteric polymer-based water treatment agents - Wei Yu; Liping Xiong; Jiaheng Teng; Cheng Chen; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Desalination, 2024)

Highly efficient and selective electrosynthesis of urea via co-reduction of carbon dioxide and nitrate over the TiN catalyst - Hongjun Fang; Ze Wang; Chen-Han Kuo; Hongsheng Yang; Xinzhen Feng; Weijie Ji; Chak-Tong Au (Chemical Engineering Journal, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

Synthesis of organic layered double hydroxide from waste bischofite and its application on ageing resistance of asphalt - Canlin Zhang; Hongjun Dong; Ting Wang; Yifei Li; Song Xu; Yun Que; Yu Chen (Fuel, 2024)

The change of coordination environments induced by vacancy defects in hematite leads to a contrasting difference between cation Pb(II) and oxyanion As(V) immobilization - Yongjin Xiang; Juan Liu; Yiwen Chen; Hongjun Zhang; Lu Ren; Bangjiao Ye; Wenfeng Tan; Kappler Andreas; Jingtao Hou (Environmental Pollution, 2024)

Effects of childhood maltreatment and major depressive disorder on functional connectivity in hippocampal subregions - Huiqin Nie; Tong Yu; Yurong Zou; Yuhong Li; Juran Chen; Jinrou Xia; Qianyi Luo; Hongjun Peng (Brain Imaging and Behavior, 2024)

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Atomically dispersed dual-atom catalysts: A new rising star in environmental remediation - Xialiang Jiang; Cheng Chen; Junjie Chen; Shuning Yu; Wei Yu; Liguo Shen; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Science of The Total Environment, 2024)

Seawater intrusion-triggered high fluoride groundwater development on the eastern coast of China - Tengfei Fu; Yushan Fu; Chenzhe Li; Minxing Dong; Chen Qi; Zhenyan Wang; Guangquan Chen; Qiao Su; Xingyong Xu; Hongjun Yu (Environmental Science and Pollution Research, 2024)

Groundwater salinization under the influence of paleo sea-level fluctuation: a case study in southern Laizhou Bay, China - Zhen Cui; Guangquan Chen; Shenliang Chen; Hongjun Yu; Keke Chen; Baichuan Ran; Tengfei Fu; Wenzhe Lyu; Yancheng Wang; Xueyan Jiang; Xihuang Zhong (Frontiers in Marine Science, 2024)
The groundwater environment in low-lying coastal regions is significantly impacted by global sea-level fluctuation. In Laizhou Bay, three large-scale transgressions have occurred since the late Pleistocene, resulting in the transformation of ancient seawater into brine. This brine has become a major contributor to groundwater salinity in the area. This study establishes a correlation between groundwater occurrence and paleoclimate changes in Laizhou Bay using borehole sediment data. The source and mechanism of groundwater salinity are analyzed based on sediment pore water characteristics and hydrogen and oxygen isotopes. The study reveals that the stratigraphic structures in the area consist of four layers: a Holocene transgressive layer, a continental confining bed from the late Pleistocene, a Cangzhou transgressive layer from the late Pleistocene, and a fluvial aquifer from the middle Pleistocene. All aquifers in the study area have been infiltrated by modern seawater, with the uppermost Holocene aquifer influenced by evaporation and leaching processes, the central late Pleistocene aquifer remaining relatively stable, and the lower middle Pleistocene aquifer affected by subsurface low salinity runoff and exhibiting an increasing trend with depth. Given the presence of numerous hydrogeological environments globally that are similar to the study area, the obtained mechanisms of groundwater salinization in this study will provide theoretical support for groundwater management in similar regions worldwide.

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

A new approach for gridded risk assessment of rainfall-triggered flood and landslide hazards over a large region based on coupled flood-landslide modelling and ensemble simulation - Sheng Wang; Ke Zhang; Lijun Chao; Guoding Chen; Yi Xia; Hongjun Bao; Chuntang Zhang (Environmental Modelling & Software, 2024)

Flexible metal membrane integrated electrified and catalytic attributes for multifunctional water purification with enhanced scaling resistance - Ning Kong; Liguo Shen; Qianqian Zeng; Cheng Chen; Jiaheng Teng; Feng Chen; Hongjun Lin (Chemical Engineering Journal, 2024)

Effects of triclosan exposure on stem cells from human exfoliated deciduous teeth (SHED) fate - Shiwen Deng; Caifeng Li; Junqi Chen; Zhao Cui; Tong Lei; Hongjun Yang; Peng Chen (Science of The Total Environment, 2023)

Membrane-catalysis integrated system for contaminants degradation and membrane fouling mitigation: A review - Cheng Chen; Lun Lu; Lingya Fei; Jiujing Xu; Boya Wang; Bisheng Li; Liguo Shen; Hongjun Lin (Science of The Total Environment, 2023)

A Cryogenian interglacial source rock in South China: Geochemistry, spatial distribution and organic matter enrichment - Peng Li; Hongjun Qu; Aiguo Wang; Shuo Chen (Precambrian Research, 2023)

Insights into synergistic metabolism of phenol and ammonium pollutants in treating coal gasification wastewater by algal-microbial fuel cell - Chengye Wang; Mengqi Zheng; Guowei Chen; Zipeng Yan; Binghan Xie; Wei Wang; Hongjun Han (Journal of Water Process Engineering, 2023)

Effects of replacement partial sodium chloride on characteristic flavor substances of bacon during storage based on GC×GC-MS and non-targeted metabolomics analyses - Jinggang Ruan; Zhicheng Wu; Jingbing Xu; Yiru Yu; Yong Tang; Xinrui Xie; Jiaxin Chen; Zhaoming Wang; Dong Zhang; Jie Tang; Hongjun Li (Food Chemistry, 2023)

AnWRKY29 from the desert xerophytic evergreen Ammopiptanthus nanus improves drought tolerance through osmoregulation in transgenic plants - Shuyao Wang; Yahui Liu; Xin Hao; Zhaoyuan Wang; Yingying Chen; Yue Qu; Hongjun Yao; Yingbai Shen (Plant Science, 2023)

Wall-proximity effects on vortex-induced vibrations of a circular cylinder - Guanghao Chen; Md. Mahbub Alam; Yu Zhou; Chunning Ji; Hongjun Zhu (Ocean Engineering, 2023)

N-doped carbon quantum dots enhance anaerobic digestion under light condition: The performances and potential mechanisms - Qiang Liu; Shuo Chen; Haoyu Zhang; Lu Feng; Hongjun Zhou; Junting Pan; Yeqing Li; Chunming Xu (Chemical Engineering Journal, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Using automated machine learning techniques to explore key factors in anaerobic digestion: At the environmental factor, microorganisms and system levels - Yi Zhang; Zhangmu Jing; Yijing Feng; Shuo Chen; Yeqing Li; Yongming Han; Lu Feng; Junting Pan; Mahmoud Mazarji; Hongjun Zhou; Xiaonan Wang; Chunming Xu (Chemical Engineering Journal, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Big data and public policy: Course, content and outcome Big data and public policy: Course, content and outcome , by Rebecca Moody and Victor Bekkers, Cham, Switzerland, Palgrave Macmillan, 2023, IX + 198 pp., $129.99 (hardcover), ISBN 9783031160301 - Hang Zhang; Hongjun Chen (The Social Science Journal, 2023)

The combination of multiple linear regression and adaptive neuro-fuzzy inference system can accurately predict trihalomethane levels in tap water with fewer water quality parameters - Jianzhen Zhang; Duo Ye; Quanyou Fu; Minjie Chen; Hongjun Lin; Xiaoling Zhou; Wenjing Deng; Zeqiong Xu; Hongjie Sun; Huachang Hong (Science of The Total Environment, 2023)

Coupled responses of the flow-induced vibration and flow-induced rotation of a rigid cylinder-plate body - Tao Tang; Hongjun Zhu; Qing Xiao; Quanyu Chen; Jiawen Zhong; Yingmei Li; Tongming Zhou (Ocean Engineering, 2023)

Assessing the performance of SWAN model for wave simulations in the Bay of Bengal - Wanwei Zhang; Hongjun Zhao; Guoping Chen; Jie Yang (Ocean Engineering, 2023)

Dissolved organic matter evolution and straw decomposition rate characterization under different water and fertilizer conditions based on three-dimensional fluorescence spectrum and deep learning - Guang Yang; Hongwei Pan; Hongjun Lei; Wenbin Tong; Lili Shi; Huiru Chen (Journal of Environmental Management, 2023)

In-situ characterization of the size distribution of lubricant droplets in rotary compressor - Puyuan Wu; Jun Chen; Paul E. Sojka; Yang Li; Hongjun Cao (International Journal of Refrigeration, 2023)

Extracellular vesicles from human umbilical cord mesenchymal stem cells prevent steroid-induced avascular necrosis of the femoral head via the PI3K/AKT pathway - Puji Peng; XueZhong Wang; Chen Qiu; Wendi Zheng; Hongjun Zhang (Food and Chemical Toxicology, 2023)

Evaluation of water depth and inundation duration on Typha domingensis sustainability in the Everglades Stormwater treatment areas: A test cell study - Orlando A. Diaz; Michael J. Chimney; Nigel A. Temple; Kristin A. Vaughan; Hongjun Chen (Ecological Engineering, 2023)

Titanium oxide nanotubes intercalated two-dimensional MXene composite membrane with exceptional antifouling and self-cleaning properties for oil/water separation - Qianqian Zeng; Die Ling Zhao; Liguo Shen; Hongjun Lin; Ning Kong; Lei Han; Cheng Chen; Jiaheng Teng; Chuyang Tang; Tai-Shung Chung (Chemical Engineering Journal, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Configuration modulation of vermiculite by exfoliation coupled Cu(II) anchoring for boosting removal of tetracycline via synergy of adsorption and photocatalysis - Ping Zhang; Mingxue Xiang; Wei Jiang; Huiling Liu; Yu Chen; Ying Fang; Longyong Wu; Hongjun Guo; Yufei Wang (Chemical Engineering Journal, 2023)

Enhanced methane yield in anaerobic digestion of waste activated sludge by combined pretreatment with fungal mash and free nitrous acid - Min Zhang; Yuwei Yang; Huaqian Mou; Aodong Pan; Xiaomei Su; Jianrong Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2023)

Compound hot extremes exacerbate forest growth decline in dry areas but not in humid areas in the Northern Hemisphere - Hongjun Yang; Wenjing Tao; Qimei Ma; Hanfeng Xu; Lingfeng Chen; Hongjun Dong; Yuchuan Yang; Nicholas G. Smith; Lei Chen (Agricultural and Forest Meteorology, 2023)

Superior performance of a membrane bioreactor through innovative in-situ aeration and structural optimization using computational fluid dynamics - Liguo Shen; Qihang Wu; Qunfeng Ye; Hongjun Lin; Jianzhen Zhang; Cheng Chen; Rong Yue; Jiaheng Teng; Huachang Hong; Bao-Qiang Liao (Water Research, 2023)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Initiation and evolution of an isolated submarine canyon system on a low-gradient continental slope - Wei Li; Shuang Li; Tiago M. Alves; Song Jing; Hongjun Chen; Wenhuan Zhan (Geomorphology, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Flexible dual-functionalized hyaluronic acid hydrogel adhesives formed in situ for rapid hemostasis - Penghui Fan; Qi Dong; Junfeng Yang; Yun Chen; Hongjun Yang; Shaojin Gu; Weilin Xu; Yingshan Zhou (Carbohydrate Polymers, 2023)

Identification of monoclonal antibody targeting epitope on p72 trimeric spike of African swine fever virus - Xulai Duan; Yingnan Liu; Zongyan Chen; Zhenhua Xie; Chuanwen Tian; Yao Li; Lu Lv; Rongrong Wang; Jingyi Liu; Hongjun Chen (Virus Genes, 2023)

Effect of the random distribution of gravel particles on the mechanical behaviors of conglomerate - Jun Wei; Hualin Liao; Bin Huang; Ning Li; Hongjun Liang; Bo Zhou; Quan Zhang; Long Chen; Hui Feng (Arabian Journal of Geosciences, 2023)

Simulation of transport mechanism of radium isotopes in aquifer on the southern coast of Laizhou Bay - Yancheng Wang; Guangquan Chen; Hongjun Yu; Xingyong Xu; Yinqiao Zou; Wenqing Zhao; Weitao Han; Wenzhe Lyu; Zhen Cui; Runtian Ding (Acta Oceanologica Sinica, 2023)

Efficient oily wastewater treatment by a novel electroflotation-membrane separation system consisting a Ni-Cu-P membrane prepared by electroless nickel plating - Jing Wang; Binghong Chen; Hongjun Lin; Renjie Li (Science of The Total Environment, 2023)

Comparation of mesophilic and thermophilic anaerobic co-digestion of food waste and waste activated sludge driven by biochar derived from kitchen waste - Rong Zhang; Min Zhang; Huaqian Mou; Zijing An; Hailu Fu; Xiaomei Su; Chongjun Chen; Jianrong Chen; Hongjun Lin; Faqian Sun (Journal of Cleaner Production, 2023)

Experimental study of the lubricant-refrigerant flow in a rotary compressor - Puyuan Wu; Jun Chen; Paul E. Sojka; Yang Li; Hongjun Cao (International Journal of Refrigeration, 2023)

Stable oxic-anoxic transitional interface is beneficial to retard soil carbon loss in drained peatland - Liangfeng Liu; Jianqing Tian; Hongjun Wang; Dan Xue; Xinya Huang; Ning Wu; Meng Wang; Xingliang Xu; Changhui Peng; Yanfen Wang; Huai Chen (Soil Biology and Biochemistry, 2023)

Novel mesocellular silica foam supported poly(amidoxime-ethyleneimine) network for fast and highly efficient uranium extraction from seawater - Jiajia Yang; Yun Li; Tian Tian; Haitao Shi; Zia Ahmad; Ningbo Geng; Jing Jin; Yanqiang Huang; Haijun Zhang; Hongjun Fan; Jiping Chen (Chemical Engineering Journal, 2023)

Plant invasion mediates the regulation of topsoil organic carbon sequestration by the fungal community in coastal wetlands - Chen Tian; Weiqi Wang; Hongjun Wang; Huai Chen; Jianqing Tian (CATENA, 2023)

Characterization and phylogenetic analysis of bovine gammaherpesvirus 4 isolated in China, 2022 - Weiqiang Guo; Tong Sun; Yingnan Liu; Xulai Duan; Chuanwen Tian; Zhou Zhou; Yong-Sam Jung; Jingyi Liu; Hongjun Chen (Virus Genes, 2023)

Deformation analysis of underwater shield tunnelling based on HSS model parameter obtained by the Bayesian approach - Yao Lu; Peng Yu; Yan Zhang; Jian Chen; Tao Liu; Han Wang; Hongjun Liu (Frontiers in Marine Science, 2023)
Deformation analysis and control of underwater large-diameter shield tunnels is a prerequisite for safe tunnel construction. Reasonable selection of constitutive model and its parameters is the key to accurately predicting the deformation induced by underwater shield tunnelling. In this paper, the finite element analysis of cavity expansion during the piezocone penetration test (CPTU) based on the hardening soil model with small strain stiffness (HSS) model was carried out, and the correlation model of the normalized cone tip resistance Q with the reference secant modulus E 50 ref and the effective internal friction angle φ ’ was established and verified using mini CPTU chamber test. Then, a Bayesian probability characterization approach for E 50 ref of silty clay based on CPTU was proposed. Furthermore, the deformation analysis of Jinan Yellow River tunnel crossing the south embankment was carried out to verify the reliability of the proposed approach. The good agreement between the field measurement and numerical simulation confirms that the parameters obtained by the Bayesian approach are reliable. Finally, a sensitivity analysis was performed to study the law of riverbed settlement induced by underwater large-diameter shield tunnelling. The results show that the increasing support pressure could effectively reduce the riverbed settlement, but there is an upper limit. The optimal support pressure of established model is between 0.45 MPa and 0.5 MPa. The uphill section causes greater riverbed settlement than the downhill section. Under the same condition, increasing buried depth and water level will lead to a more significant settlement.

Micropore sites in ferrihydrite are responsible for its higher affinity towards As(III) relative to As(V) - Qian Zheng; Shuxin Tu; Yiwen Chen; Hongjun Zhang; William Hartley; Bangjiao Ye; Lu Ren; Juan Xiong; Wenfeng Tan; Andreas Kappler; Jingtao Hou (Geochimica et Cosmochimica Acta, 2023)

Surface selenation engineering on metal cocatalysts for highly efficient photoreduction of carbon dioxide to methanol - Wenbin Chen; Shijie Wu; Liyan Xie; Yujie Wu; Yanwen Ye; Huigang Wang; Zhulei Chen; Hongjun Lin; Leihong Zhao; Song Bai (Chemical Engineering Journal, 2023)

Reveal the major factors controlling quinolone adsorption on mesoporous carbon: Batch experiment, DFT calculation, MD simulation, and machine learning modeling - Hongjun Zhao; Yitao Lyu; Jingrun Hu; Min Li; Huan Chen; Yi Jiang; Moran Tang; Yang Wu; Weiling Sun (Chemical Engineering Journal, 2023)

Interactions Between Humic Acid and the Forms and Bioavailability of Copper in Water - Hongwei Pan; Lili Shi; Xin Liu; Hongjun Lei; Guang Yang; Huiru Chen (Water, Air, & Soil Pollution, 2023)

Relationship between pepper (Capsicum annuum L.) root morphology, inter-root soil bacterial community structure and diversity under water–air intercropping conditions - Hongjun Lei; Cuicui Jin; Zheyuan Xiao; Jian Chen; Shah Jahan Leghari; Hongwei Pan (Planta, 2023)

The Complete Genome Sequence of a Gossypol-Degrading Bacterial Strain, Raoultella sp. YL01 - Si Chen; Weishu Zhang; Huiling Zhang; Ying Cui; Feng Wang; Jing Wu; Hongjun Chao; Dazhong Yan (Current Microbiology, 2023)

Sufentanil combined with parecoxib sodium inhibits proliferation and metastasis of HER2-positive breast cancer cells and regulates epithelial-mesenchymal transition - Sunmian Xu; Xiaohui Li; Wenbin Li; Nina Ma; Hongjun Ma; Jian Cui; Xiaogang You; Xuexin Chen (Clinical & Experimental Metastasis, 2023)

Safe Design of a Hydrogen-Powered Ship: CFD Simulation on Hydrogen Leakage in the Fuel Cell Room - Wenfeng Guan; Ju Chen; Lijian Chen; Jiaolong Cao; Hongjun Fan (Journal of Marine Science and Engineering, 2023)
Adopting proton exchange membrane fuel cells fuelled by hydrogen presents a promising solution for the shipping industry’s deep decarbonisation. However, the potential safety risks associated with hydrogen leakage pose a significant challenge to the development of hydrogen-powered ships. This study examines the safe design principles and leakage risks of the hydrogen gas supply system of China’s first newbuilt hydrogen-powered ship. This study utilises the computational fluid dynamics tool FLACS to analyse the hydrogen dispersion behaviour and concentration distributions in the hydrogen fuel cell room based on the ship’s parameters. This study predicts the flammable gas cloud and time points when gas monitoring points first reach the hydrogen volume concentrations of 0.8% and 1.6% in various leakage scenarios, including four different diameters (1, 3, 5, and 10 mm) and five different directions. This study’s findings indicate that smaller hydrogen pipeline diameters contribute to increased hydrogen safety. Specifically, in the hydrogen fuel cell room, a single-point leakage in a hydrogen pipeline with an inner diameter not exceeding 3 mm eliminates the possibility of flammable gas cloud explosions. Following a 10 mm leakage diameter, the hydrogen concentration in nearly all room positions reaches 4.0% within 6 s of leakage. While the leakage diameter does not impact the location of the monitoring point that first activates the hydrogen leak alarm and triggers an emergency hydrogen supply shutdown, the presence of obstructions near hydrogen detectors and the leakage direction can affect it. These insights provide guidance on the optimal locations for hydrogen detectors in the fuel cell room and the pipeline diameters on hydrogen gas supply systems, which can facilitate the safe design of hydrogen-powered ships.

Hydrochemical characteristics and quality assessment of groundwater in Guangxi coastal areas, China - Tengfei Fu; Chenzhe Li; Zhenyan Wang; Chen Qi; Guangquan Chen; Yushan Fu; Qiao Su; Xingyong Xu; Wenquan Liu; Hongjun Yu (Marine Pollution Bulletin, 2023)

Developmental dynamics and survival characteristics of the common horse bot flies (Diptera, Gasterophilidae, Gasterophilus) in desert steppe - Ke Zhang; Zhongrui Ju; Yu Zhang; Chen Wang; Shalitanati Mubalake; Dini Hu; Dong Zhang; Kai Li; Hongjun Chu (Veterinary Parasitology, 2023)

Start-up phase optimization of pyrite-intensified hybrid sequencing batch biofilm reactor (PIHSBBR): Mixotrophic denitrification performance and mechanism - Wentao Zhu; Jing Chen; Hongjun Zhang; Sicheng Yuan; Weijie Guo; Qian Zhang; Shiyang Zhang (Journal of Environmental Management, 2023)

Advances in technology and utilization of natural resources for achieving carbon neutrality and a sustainable solution to neutral environment - Saleem Raza; Ehsan Ghasali; Muslim Raza; Cheng Chen; Bisheng Li; Yasin Orooji; Hongjun Lin; Ceren Karaman; Hassan Karimi Maleh; Nevin Erk (Environmental Research, 2023)

Graphene oxide assisted assembly of superhydrophilic MOF-based membrane with 2D/3D hybrid nanochannels for enhanced water purification - Lingya Fei; Cheng Chen; Liguo Shen; Yuyao Zhang; Boya Wang; Jiujing Xu; Bisheng Li; Saleem Raza; Hongjun Lin (Chemical Engineering Journal, 2023)

Effects of shellfish culture on the community and mortality of zooplankton in a subtropical Bay - Bijian Pang; Hongjun Li; Mingmin Li; Xin Luo; Ying Chen; Tianshen Li; Wenlu Lan (Journal of Oceanology and Limnology, 2023)

Impacts of heatwaves and cold spells on glaucoma in rural China: a national cross-sectional study - Ai Zhang; Qihua Wang; Xueli Yang; Yuanyuan Liu; Jiayu He; Anqi Shan; Naixiu Sun; Qianfeng Liu; Baoqun Yao; Fengchao Liang; Ze Yang; Xiaochang Yan; et al. (Environmental Science and Pollution Research, 2023)
China faces increasing health risks from climate change. The structure and function of the eye and vision were affected by extreme heat and cold. The study aimed to evaluate the impacts of heatwaves and cold spells on glaucoma. A national cross-sectional study of the Rural Epidemiology for Glaucoma (REG-China) was conducted in ten provinces of China, and 36,081 adults aged 40 years or more were included. Glaucoma signs were assessed via a standard examination. A total of 15 heatwave definitions, based on intensity (95th to 99th percentiles of temperature distribution) and duration (≥2 days, 3 days, and 4 days), were used to quantify heatwave effects, and 6 cold spell definitions were defined based on threshold temperature percentile (5th and 10th) and duration (3 days, 5 days, and 9 days). Multivariable-adjusted logistic regression models paired with interaction analysis were performed to investigate the impacts of heatwaves and cold spells on glaucoma, and the dose-response relationships were assessed using a restricted cubic spline (RCS) model. Subgroup analysis was conducted stratified by gender, age, smoking status, occupation, and family history of glaucoma. The overall prevalence of glaucoma was 2.1% (95% CI 1.94–2.25%). Higher heatwaves were significantly correlated with higher OR of glaucoma, with the OR (95% CI) ranging from 1.014 (1.009, 1.018) to 1.090 (1.065, 1.115) by different definitions. Glaucoma was affected by heatwaves more strongly than by cold spells. The effects of both heatwaves and cold spells were higher in males than females and in smokers than nonsmokers. These results of the present study evoked the attention of prospective research to elucidate the relationship between extreme temperatures and eye diseases.

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

Flow structures around a circular cylinder with bilateral splitter plates and their dynamic characteristics - Hongjun Zhu; Quanyu Chen; Tao Tang; Md. Mahbub Alam; Tongming Zhou (Ocean Engineering, 2023)

Dual-crosslinked hyaluronic acid hydrogel with self-healing capacity and enhanced mechanical properties - Mengfan Zhang; Xiao Chen; Kaidan Yang; Qi Dong; Hongjun Yang; Shaojin Gu; Weilin Xu; Yingshan Zhou (Carbohydrate Polymers, 2023)

CircRNA3616 knockdown attenuates inflammation and apoptosis in spinal cord injury by inhibiting TLR4/NF-κB activity via sponging miR-137 - Li Wang; Zhiwen Song; Hongjun Zou; Haining Chen; Yong Hu; Xiangnan Li; Jinbo Liu (Molecular and Cellular Biochemistry, 2023)

Alkali-catalyzed hydrothermal oxidation treatment of triclosan in soil: Mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Hongjun Luo; Rong Zhang; Yafei Hu; Haijiao Xie; Neng-min Zhu (Science of The Total Environment, 2023)

Efficient oil-water emulsion treatment via novel composite membranes fabricated by CaCO3-based biomineralization and TA-Ti(IV) coating strategy - Hongli Xie; Binghong Chen; Hongjun Lin; Renjie Li; Liguo Shen; Genying Yu; Lining Yang (Science of The Total Environment, 2023)

Helical configuration channels boost performance in anion exchange membranes - Yang Zhang; Fan Zhang; Yiwen Chen; Lixuan Sun; Chengpeng Wei; Huaqing Zhang; Hongjun Zhang; Bangjiao Ye; Liang Wu; Xiaolin Ge; Tongwen Xu (Chemical Engineering Journal, 2023)

The coupling of persulfate activation and membrane separation for the effective pollutant degradation and membrane fouling alleviation - Mingzhu Zhou; Junjie Chen; Shuning Yu; Binghong Chen; Cheng Chen; Liguo Shen; Bisheng Li; Hongjun Lin (Chemical Engineering Journal, 2023)

CMC based microcapsules for smart delivery of pesticides with reduced risks to the environment - Ming Zhao; Zhenhai Chen; Li Hao; Huayao Chen; Xinhua Zhou; Hongjun Zhou (Carbohydrate Polymers, 2023)

The complete chloroplast genome of the medical plant Huperzia crispata from the Huperziaceae family: structure, comparative analysis, and phylogenetic relationships - Dengpan Yin; Bo Pang; Haibo Li; Qiao Liu; Yufeng Zhai; Nan Ma; Tongtong Chen; Hongjun Shen; Qiaojun Jia; Dekai Wang (Molecular Biology Reports, 2022)

Nitrate and sodium nitroprusside alter the development of Asian black-spined toads’ embryos by inducing nitric oxide production - Hongjun Chen; Yuting Pang; Yunqi Wei; Xinni He; Yongpu Zhang; Lei Xie (Environmental Science and Pollution Research, 2022)

Aberrant brain connectivity is associated with childhood maltreatment in individuals with major depressive disorder - Qianyi Luo; Juran Chen; Yuhong Li; Zhiyao Wu; Xinyi Lin; Jiazheng Yao; Huiwen Yu; Huawang Wu; Hongjun Peng (Brain Imaging and Behavior, 2022)

Origin and Implications of Pollution in Coastal Groundwater of the Guangdong Province - Chenzhe Li; Tengfei Fu; Yushan Fu; Zhenyan Wang; Bin Li; Chen Qi; Guangquan Chen; Xingyong Xu; Hongjun Yu (Journal of Marine Science and Engineering, 2022)
The groundwater resource is crucial to the urbanization and industrialization in the Guangdong coastal area; the rapid development of Daya Bay has presented a challenge for the management of the groundwater quantity and quality. Therefore, a novel approach to hydrochemical analysis, which, combined with the health risk model and the water quality index (WQI), was used to explain the hydrochemistry characteristics and risks to human health of groundwater in the Guangdong coastal areas in addition to investigating the factors controlling groundwater quality. The results showed that the average concentration of total dissolved solids (TDS) in groundwater was 1935.26 mg/L and the quality of water was weakly alkaline. The dominant hydrochemical types of groundwater were identified to be Mg-HCO3 and Na-Cl·HCO3. The main factor influencing the hydrochemical composition was rock weathering, while the result of principal component analysis (PCA) shows seawater intrusion and anthropogenic inputs also have an effect on the water quality. The conclusions of the water quality assessment indicated that most of the groundwater samples were acceptable for drinking. However, both WQI and the non-carcinogenic hazard quotient (HQ) values indicated unacceptable risks in any area of Maoming, Zhanjiang and Shantou, and, according to the hazard index (HI) value, children in the study area are at more danger to health risks than adults. It is suggested that both groundwater salinization and nitrate pollution should be paid attention to when improving groundwater quality and exploring the sustainable utilization of groundwater resources.

Distribution characteristics of delta reservoirs reshaped by bottom currents: A case study from the second member of the Yinggehai Formation in the DF1-1 gas field, Yinggehai Basin, South China Sea - Shuo Chen; Renhai Pu; Huiqiong Li; Hongjun Qu; Tianyu Ji; Siyu Su; Yunwen Guan; Hui Zhang (Acta Oceanologica Sinica, 2022)

Estimating Seismic Intensity Maps of the 2021 Mw 7.3 Madoi, Qinghai and Mw 6.1 Yangbi, Yunnan, China Earthquakes - Wenkai Chen; Dun Wang; Can Zhang; Qiang Yao; Hongjun Si (Journal of Earth Science, 2022)

Daytime warming triggers tree growth decline in the Northern Hemisphere - Wenjing Tao; Kangshan Mao; Jiang He; Nicholas G. Smith; Yuxin Qiao; Jing Guo; Hongjun Yang; Wenzhi Wang; Jianquan Liu; Lei Chen (Global Change Biology, 2022)
Global warming has been linked to declines in tree growth. However, it is unclear how the asymmetry in daytime and nighttime warming influences this response. Here, we use 2947 residual tree‐ring width chronologies covering 32 species at 2493 sites, between 1901 and 2018, across the Northern Hemisphere, to analyze the effects of daytime and nighttime temperatures, precipitation, and drought stress on the radial growth of trees. We show that drought stress was primarily triggered by daytime rather than nighttime warming. The radial growth of trees was more sensitive to drought stress in warm regions than in cold regions, especially for angiosperms. Our study provides robust evidence that daytime warming is the primary driver of the observed declines in forest productivity related to drought stress and that daytime and nighttime warming should be considered separately when modelling forest–climate interactions and feedbacks in a future, warmer world.

Numerical Study of Local Scour around Tripod Foundation in Random Waves - Ruigeng Hu; Xiuhai Wang; Hongjun Liu; Da Chen (Journal of Marine Science and Engineering, 2022)
In this study, the local scour around tripods in random waves is numerically investigated. The seabed-tripod-fluid numerical model with an RNG k−ε turbulence model is built and validated. Following that, the scour characteristics and flow velocity distribution are analyzed using the present numerical model. Finally, a revised stochastic model is proposed to predict the equilibrium scour depth, Seq, around tripods in random waves. The results indicate that the present seabed-tripod-fluid numerical model is capable of depicting the scour process and of capturing the flow field around tripods with high accuracy. Due to the blockage effects of the main column and structural elements, there is enhanced flow acceleration underneath the main column and the lower diagonal braces, which increases the turbulence intensity and seabed shear stress, causing more particles to be mobilized and transported, resulting in more severe scour at the site. The revised stochastic model shows the best agreement with the numerical and experimental results when n = 20, but more experimental data and numerical results are still needed to verify the adaptation of the revised stochastic model for larger Keulegan–Carpenter (KC) number conditions (KCrms,a > 4).

Multiple-Stage Mineralization in the Huayangchuan U−REE−Mo−Cu−Fe Ore Belt of the Qinling Orogen, Central China: Geological and Re−Os Geochronological Constraints - Hongjun Jiang; Chunsi Yang; Dequan Wang; Hui Zheng; Jie Li; Huayong Chen (Journal of Earth Science, 2022)
The Huayangchuan ore belt is located in the western segment of Xiaoqinling Orogen in the southern margin of the North China Craton (NCC), and hosts voluminous magmatism and significant U−REE−Mo−Cu−Fe polymetallic mineralization. However, geochronological framework of the various mineralization phases in this region is poorly understood. Here, we present new Re−Os isochron ages on magnetite from the Caotan Fe deposit (2 675 ± 410 Ma, MSWD = 0.55), and on pyrite from the Jialu REE deposit (2 127 ± 280 Ma, MSWD = 1.9) and Yuejiawa Cu deposit (418 ± 23 Ma, MSWD = 11.5), and Re−Os weighted average model age on pyrite from the Taoyuan Mo−U deposit (235 ± 14 Ma, MSWD = 0.17). These ages, combined with regional geology and mineralization ages from other deposits, suggest that mineralization in the Huayangchuan ore belt lasted from the Neoarchean to the Late Mesozoic. The mineralization corresponds to regional tectono-magmatic events, including the Neoar-chean alkali magmatism (REE mineralization), Paleoproterozoic plagioclase-amphibolite emplacement (Fe mineralization), Paleoproterozoic pegmatite magmatism (U mineralization), Paleozoic Shangdan oceanic slab subduction-related arc magmatism (Cu mineralization), Early Mesozoic Paleo-Tethys Ocean subduction-related arc magmatism (Mo−U mineralization), and Late Mesozoic Paleo-Pacific oceanic plate subduction direction change-related Mo(-Pb) mineralization. We proposed that the Huayang-chuan ore belt has undergone prolonged metallogenic evolution, and the magmatism and associated mineralization were controlled by regional geodynamic events.

Molecular characterization, expression, and apoptosis regulation of siva1 in protogynous hermaphrodite fish ricefield eel (Monopterus albus) - Zhi He; Faqiang Deng; Zhijun Ma; Qian Zhang; Jiayang He; Lijuan Ye; Hongjun Chen; Deying Yang; Liang He; Jie Luo; Taiming Yan (Fish Physiology and Biochemistry, 2021)

TREM-1 aggravates chronic obstructive pulmonary disease development via activation NLRP3 inflammasome-mediated pyroptosis - Lijing Wang; Qiong Chen; Qiao Yu; Jian Xiao; Hongjun Zhao (Inflammation Research, 2021)

Patients with first-episode untreated schizophrenia who experience concomitant visual disturbances and auditory hallucinations exhibit co-impairment of the brain and retinas—a pilot study - Chuanjun Zhuo; Bo Xiao; Feng Ji; Xiaodong Lin; Deguo Jiang; Hongjun Tian; Yong Xu; Wenqiang Wang; Ce Chen (Brain Imaging and Behavior, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Bilinear neural network with 3-D attention for brain decoding of motor imagery movements from the human EEG - Chen-Chen Fan; Hongjun Yang; Zeng-Guang Hou; Zhen-Liang Ni; Sheng Chen; Zhijie Fang (Cognitive Neurodynamics, 2021)

Differences in functional connectivity density among subtypes of schizophrenic auditory hallucination - Chuanjun Zhuo; Gongying Li; Feng Ji; Ce Chen; Deguo Jiang; Xiaodong Lin; Yong Xu; Hongjun Tian; Lina Wang; Chunhua Zhou; Xiao Lin (Brain Imaging and Behavior, 2020)

Common and distinct global functional connectivity density alterations in patients with bipolar disorder with and without auditory verbal hallucination during major depressive episodes - Lixue Qiu; Jaen Ye; Feng Ji; Gang Li; Gongying Li; Xiaoyan Ma; Ranli Li; Hongjun Tian; Lina Wang; Guangdong Chen; Yong Xu; Wenqiang Wang; et al. (Brain Imaging and Behavior, 2020)

Without insight accompanied with deteriorated brain functional alterations in healthy individuals with auditory verbal hallucinations: a pilot study - Chuanjun Zhuo; Feng Ji; Xiaodong Lin; Hongjun Tian; Lina Wang; Sha Liu; Hong Sang; Wenqiang Wang; Chunmian Chen (Brain Imaging and Behavior, 2020)
Few studies have reported on brain functional differences between healthy individuals with auditory verbal hallucinations (Hi-AVH) with and without insight, so we designed a study to address this knowledge gap. We enrolled 12 Hi-AVH with insight, 15 Hi-AVH without insight, and 15 AVH-free controls (Healthy controls). Global functional connectivity density (gFCD) mapping was used to estimate brain networks. We found that the most common alterations in both Hi-AVH groups were increased gFCD in superior parietal lobule and superior temporal gyrus. We also found that distinct brain functional patterns of Hi-AVH without insight comprised lower gFCD in the frontal lobe oculomotor area, dorsolateral prefrontal cortex, supramarginal gyrus, primary auditory cortex, sensorimotor cortex, ventral anterior, and posterior cingulate Our pilot findings support the hypothesis that abnormal reciprocal action in the circuits for processing perception, memory, language, and attentional control may be pathological features of auditory verbal hallucinations.

Double decomposition and optimal combination ensemble learning approach for interval-valued AQI forecasting using streaming data - Zicheng Wang; Liren Chen; Jiaming Zhu; Huayou Chen; Hongjun Yuan (Environmental Science and Pollution Research, 2020)

Modeling of power sector decarbonization in China: comparisons of early and delayed mitigation towards 2-degree target - Huan Wang; Wenying Chen; Hongjun Zhang; Nan Li (Climatic Change, 2020)

Magnetic properties indicate the sources of hadal sediments in the Yap Trench, northwest Pacific Ocean - Yu Chen; Jichao Yang; Olusegun A. Dada; Yaomin Yang; Zhen Lin; Zhen Cui; Yue Xu; Hongjun Yu; Baohua Liu (Journal of Oceanology and Limnology, 2020)

Study on the Influence of Mud Properties on the Stability of Excavated Face of Slurry Shield and the Quality of Filter Cake Formation - Hu Wang; Jian Chen; Hongjun Liu; Lei Guo; Yao Lu; Xiuting Su; Yongmao Zhu; Tao Liu (Journal of Marine Science and Engineering, 2020)
In the construction of subsea tunnels, the stability and control of the excavation surface are the main concerns of the engineering community. In this paper, the Xiamen Metro Line 2 is used as the study case. The filter cake formation of mud shields is experimentally studied, and the excavation surface is numerically simulated. It is found that the formation of filter cake does not require a large pressure difference, and can be formed under 0.06 MPa. With the increase of pressure, the quality of filter cake is further improved, and a small amount of seawater (volume ratio less than 3%) also has a significant effect on the viscosity of mud. Under different cross-section geological conditions, with the decrease of the support pressure of the excavation face, the vertical displacement and vertical (Y-direction) displacement of the excavation face dome gradually increase, the maximum longitudinal displacement is 9.7 mm, the maximum longitudinal displacement can reach 23.9 mm, and the growth trend is nonlinear. According to different stratum conditions, during the excavation of the tunnel, the plastic area of the excavation face is different.

Phylodynamic analysis of two amino acid substitutions in the hemagglutinin protein of canine distemper virus strains detected in fur-bearing animals in China - Rongshan Tao; Hengxing Ba; Jie Chen; Mengjia Liu; Hongjun Pan; Xue Li; Quankai Wang; Jianjun Zhao (Virus Genes, 2020)

Enzyme and pH dual-responsive avermectin nano-microcapsules for improving its efficacy - Guanghua Liu; Guanquan Lin; Xida Lin; Hongjun Zhou; Huayao Chen; Li Hao; Xinhua Zhou (Environmental Science and Pollution Research, 2019)

Low-frequency fluctuation characteristics in rhesus macaques with SIV infection: a resting-state fMRI study - Jing Zhao; Feng Chen; Meiji Ren; Li Li; Aixin Li; Bin Jing; Hongjun Li (Journal of NeuroVirology, 2019)

The Feasibility of Mining Under a Water Body Based on a Fuzzy Neural Network - Hongjun Guo; Ming Ji; Kai Chen; Zongliang Zhang; Yidong Zhang; Minglei Zhang (Mine Water and the Environment, 2018)

Population genetic patterns of the solitary tunicate, Molgula manhattensis, in invaded Chinese coasts: large-scale homogeneity but fine-scale heterogeneity - Yiyong Chen; Shiguo Li; Yaping Lin; Hongjun Li; Aibin Zhan (Marine Biodiversity, 2018)

Stability analysis of suction bucket foundations under wave cyclic loading and scouring - Xuguang Chen; Tao Liu; Yuke Jiang; Hongjun Liu; Hailei Kou; Jianpeng Xu; Xixi Liu; Jinzhong Liu; Tianchi Ma; Tao Feng; Xiaodong Niu (Marine Georesources & Geotechnology, 2018)

Examining stability of independent component analysis based on coefficient and component matrices for voxel-based morphometry of structural magnetic resonance imaging - Qing Zhang; Guoqiang Hu; Lili Tian; Tapani Ristaniemi; Huili Wang; Hongjun Chen; Jianlin Wu; Fengyu Cong (Cognitive Neurodynamics, 2018)

Comprehensive investigation of submarine slide zones and mass movements at the northern continental slope of South China Sea - Hongjun Chen; Jin Liang; Yuehua Gong (Journal of Ocean University of China, 2018)

Seismic analysis of early-mid Miocene carbonate platform in the southern Qiongdongnan Basin, South China Sea - Xiaochuan Wu; Renhai Pu; Ying Chen; Hongjun Qu; Huailei Shen (Acta Oceanologica Sinica, 2018)

Optimized extreme learning machine for urban land cover classification using hyperspectral imagery - Hongjun Su; Shufang Tian; Yue Cai; Yehua Sheng; Chen Chen; Maryam Najafian (Frontiers of Earth Science, 2017)

Alternative reverse genetics system for influenza viruses based on a synthesized swine 45S rRNA promoter - Kai Wang; Qi Huang; Zhiwei Yang; Kezong Qi; Hongmei Liu; Hongjun Chen (Virus Genes, 2017)

Occurrence of submarine canyons, sediment waves and mass movements along the northern continental slope of the South China Sea - Hongjun Chen; Wenhuan Zhan; Liqing Li; Ming-ming Wen (Journal of Earth System Science, 2017)

Dynamic equity carbon permit allocation scheme to limit global warming to two degrees - Lining Wang; Wenying Chen; Hongjun Zhang; Ding Ma (Mitigation and Adaptation Strategies for Global Change, 2017)

Model test and stress distribution law of unsymmetrical loading tunnel in bedding rock mass - Xinrong Liu; Hongjun Chen; Kun Liu; Chunmei He (Arabian Journal of Geosciences, 2017)

Response of geomorphic and geological processes to insufficient and ample sediment supply along the upper continental slope in the north-western South China Sea - Hongjun Chen; Wenhuan Zhan; Shiguo Wu (Journal of Earth System Science, 2016)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

Molecular variation and expansion of a rice black-streaked dwarf virus population based on analysis of segment 1 in Jining, China - Yu Zhou; Qingchang Meng; Yanping Chen; Jirong Wu; Zhuanfang Hao; Zhenhua Wang; Degui Zhang; Mingshun Li; Hongjun Yong; Shihuang Zhang; Xinhai Li; Jianfeng Weng (Archives of Virology, 2016)

Distinct Hippocampal Expression Profiles of lncRNAs in Rats Exhibiting a PTSD-like Syndrome - Liu Qingzhen; Ma Jiehua; Yu Zhiyang; Liu Hongjun; Chen Chunlong; Li Weiyan (Molecular Neurobiology, 2016)

Towards low carbon development in China: a comparison of national and global models - Wenying Chen; Xiang Yin; Hongjun Zhang (Climatic Change, 2016)

Microalgal industry in China: challenges and prospects - Jun Chen; Yan Wang; John R. Benemann; Xuecheng Zhang; Hongjun Hu; Song Qin (Journal of Applied Phycology, 2016)

The potential geographic distribution of Bactrocera correcta (Diptera: Tephrididae) in China based on eclosion rate model - Yujia Qin; Wenlong Ni; Jiajiao Wu; Zihua Zhao; Hongjun Chen; Zhihong Li (Applied Entomology and Zoology, 2015)

Experimental evaluation of calcein and alizarin red S for immersion marking grass carp Ctenopharyngodon idellus - Hongjian Lü; Hongjun Chen; Mei Fu; Xiwen Peng; Dan Xi; Zhixin Zhang (Fisheries Science, 2015)

Hyperspectral image classification based on volumetric texture and dimensionality reduction - Hongjun Su; Yehua Sheng; Peijun Du; Chen Chen; Kui Liu (Frontiers of Earth Science, 2015)

Paleoenvironmental changes during the late Quaternary as inferred from foraminifera assemblages in the Laizhou Bay - Jing Yao; Hongjun Yu; Xingyong Xu; Liang Yi; Guangquan Chen; Qiao Su (Acta Oceanologica Sinica, 2014)

Influence of Inundation Depth on Typha domingensis and its Implication for Phosphorus Removal in the Everglades Stormwater Treatment Area - Hongjun Chen; Kristin Vaughan (Wetlands, 2014)

Genetic and physical fine mapping of the novel brown midrib gene bm6 in maize (Zea mays L.) to a 180 kb region on chromosome 2 - Yongsheng Chen; Hongjun Liu; Farhad Ali; M. Paul Scott; Qing Ji; Ursula Karoline Frei; Thomas Lübberstedt (Theoretical and Applied Genetics, 2012)

Factors affecting summer maize yield under climate change in Shandong Province in the Huanghuaihai Region of China - Guoqing Chen; Hongjun Liu; Jiwang Zhang; Peng Liu; Shuting Dong (International Journal of Biometeorology, 2012)

Whole genome sequencing and biological characterization of Duck/JS/10, a new lentogenic class I Newcastle disease virus - Chunchun Meng; Xvsheng Qiu; Shiqiang Jin; Shengqing Yu; Hongjun Chen; Chan Ding (Archives of Virology, 2012)

Membrane Bioreactors for Industrial Wastewater Treatment: A Critical Review - Hongjun Lin; Weijue Gao; Fangang Meng; Bao-Qiang Liao; Kam-Tin Leung; Leihong Zhao; Jianrong Chen; Huachang Hong (Critical Reviews in Environmental Science and Technology, 2012)

Enzymatic and biological characteristics of enolase in Brucella abortus A19 - Xiangan Han; Chan Ding; Hongjun Chen; Qinghai Hu; Shengqing Yu (Molecular Biology Reports, 2012)

The expression of Na, K-ATPase in Litopenaeus vannamei under salinity stress - Hongyan Sun; Lvping Zhang; Chunhua Ren; Chang Chen; Sigang Fan; Jian Jun Xia; Hongjun Lin; Chaoqun Hu (Marine Biology Research, 2011)

Surface-Flow Constructed Treatment Wetlands for Pollutant Removal: Applications and Perspectives - Hongjun Chen (Wetlands, 2011)

Construction of mini-Tn4001 transposon vector for Mycoplasma gallisepticum - HongJun Chen; ChunMei Zhao; XieYue Shen; DanQing Chen; ShengQing Yu; Chan Ding (Science China Life Sciences, 2010)

Effect of Flooding Depth on Growth, Biomass, Photosynthesis, and Chlorophyll Fluorescence of Typha domingensis - Hongjun Chen; Manuel F. Zamorano; Delia Ivanoff (Wetlands, 2010)

MDV-1 VP22: a transporter that can selectively deliver proteins into cells - Chenfei Zhang; Aijian Qin; Hongjun Chen; Xufang Deng; Yuwen Su; Kun Qian (Archives of Virology, 2009)

The effect of mutation of F87 on the properties of CYP102A1-CYP4C7 chimeras: altered regiospecificity and substrate selectivity - Chiung-Kuang J. Chen; Tatiana Kh. Shokhireva; Robert E. Berry; Hongjun Zhang; F. Ann Walker (JBIC Journal of Biological Inorganic Chemistry, 2008)

Effects of phosphate availability and redox intensity on growth and nutrient uptake of Rhynchospora tracyi, a wet prairie species in the everglades - Hongjun Chen; Irving A. Mendelssohn; Bent Lorenzen; Hans Brix; ShiLi Miao (Wetlands, 2008)